Psycheutopia: an innovative educational program to enhance mental health literacy among medical students - Jabari, Zahra; Eslami, Mohammad; Jalali Nadoushan, Amir Hossein; Goharinezhad, Salime; Tavallaei, MohammadJavad; Khodadoust, Elaheh; Mahmoodi, Seyed Mohammad Hossein (Frontiers in Psychiatry, 2025)
IntroductionMedical students face a high prevalence of mental disorders, such as depression, alongside inadequate mental health literacy (MHL). This study investigates the feasibility, and efficacy of an interactive, gamified educational program in improving participants’ MHL.MethodThirty-two Iranian medical students participated in a semi-experimental pretest-post-test study. An 18-hour online program, delivered using the flipped classroom method, focused on mental health first aid, stigma, stress management, and subjective well-being (SWB) skills. Participants were evaluated before, after, and four months post-program using the Mental Health Literacy Scale (MHLS), Mental Health Promoting Knowledge (MHPK), and World Health Organization-5 Well-being Index (WHO-5).ResultsParticipants' mean age was 22.78 ( ± 4.54). Post-test results showed significant improvement in MHLS and MHPK scores (P-values< 0.05), which were sustained at the four-month follow-up (P-values>0.01). SWB improved in the post-test evaluation (P-value= 0.058).ConclusionThe educational program effectively improved medical undergraduates’ MHL and SWB. Given the rising concerns about medical students’ mental health, implementing such curricula appears promising for long-term benefits.